Ethnobotany, phytochemistry and pharmacological properties of Fagopyri Dibotryis Rhizoma: A review - Geng, Qi; Liu, Bin; Cao, Zhiwen; Li, Li; Lu, Peipei; Lin, Lin; Yan, Lan; Lu, Cheng (Frontiers in Pharmacology, 2023)
Abstract Fagopyri Dibotryis Rhizoma (FDR) is an effective Chinese herbal medicine with a long history of use in China. FDR is effective in heat clearing and detoxifying, promotion of blood circulation, relieving carbuncles, dispelling wind, and removing dampness. Its seeds also have high nutritional value, are rich in protein, and contain a variety of mineral elements and vitamins. Therefore, FDR is considered a natural product with medical and economic benefits, and its chemical composition and pharmacological activity are of interest to scientists. The current review provides an overview of the available scientific information on FDR, particularly its botany, chemical constituents, and pharmacological activities. Various sources of valid and comprehensive relevant information were consulted, including the China National Knowledge Infrastructure, Web of Science, and PubMed. Among the keywords used were “Fagopyri Dibotryis Rhizoma”, “botanical features”, “chemical composition”, and “pharmacological activity” in combination. Various ailments are treated with FDR, such as diabetes, tumor, sore throat, headache, indigestion, abdominal distension, dysentery, boils, carbuncles, and rheumatism. FDR is rich in organic acids, tannins, flavonoids, steroids, and triterpenoids. Experiments performed in vitro and in vivo showed that FDR extracts or fractions had a wide range of pharmacological activities, including antitumor, anti-inflammatory, immunomodulatory, antioxidant, antimicrobial, and antidiabetic. The current review provides an integrative perspective on the botany, phytochemistry and pharmacological activities of FDR. FDR may be used as a medicine and food. Based on its chemical composition and pharmacological effects, the main active ingredients of FDR are organic acids, tannins, and flavonoids, and it has obvious antitumor pharmacological activity against a variety of malignant tumors. Therefore, FDR is worthy of further study and application as a potential antitumor drug.